2019
DOI: 10.1016/j.jhep.2019.03.020
|View full text |Cite
|
Sign up to set email alerts
|

The circadian clock and liver function in health and disease

Abstract: Each day, all organisms are subjected to changes in light intensity because of the Earth's rotation around its own axis. To anticipate this geo-physical variability, and to appropriately respond biochemically, most species, including mammals, have evolved an approximate 24-hour endogenous timing mechanism known as the circadian clock (CC). The 'clock' is self-sustained, cell autonomous and present in every cell type. At the core of the clock resides the CC-oscillator, an exquisitely crafted transcriptional-tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
125
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(128 citation statements)
references
References 142 publications
(322 reference statements)
0
125
0
Order By: Relevance
“…The following mechanisms may explain the association between rotating night shift work and NAFLD. As the core organ of human metabolism, the liver’s metabolic homoeostasis is regulated by the circadian clock 33. Bile acid dysregulation due to chronic circadian disruption can lead to an imbalance of nutrient use and storage 34.…”
Section: Discussionmentioning
confidence: 99%
“…The following mechanisms may explain the association between rotating night shift work and NAFLD. As the core organ of human metabolism, the liver’s metabolic homoeostasis is regulated by the circadian clock 33. Bile acid dysregulation due to chronic circadian disruption can lead to an imbalance of nutrient use and storage 34.…”
Section: Discussionmentioning
confidence: 99%
“…This liver‐specific rhythm was dependent on light‐dark cycle, indicating that the liver may have independent circadian rhythms and functions . Since circadian rhythms regulate various physiological events throughout the body, the association of disrupted circadian rhythms with human disorders including liver diseases has been suggested …”
Section: Introductionmentioning
confidence: 99%
“…5 Since circadian rhythms regulate various physiological events throughout the body, the association of disrupted circadian rhythms with human disorders including liver diseases has been suggested. 7,8 Melatonin (N-acetyl-5-methoxytryptamine) is a hormone associated with circadian rhythms especially in the dark phase. Melatonin synthesis is facilitated at night and inhibited by light at daytime detected by retinas.…”
Section: Introductionmentioning
confidence: 99%
“…The disruption of the circadian clock is detrimental to liver functions. 32 Our study revealed that in the case of dysregulated metabolic functions, with multiple influencing factors, sleep duration was still independently related to the progress of fatty liver disease, which highlighted the importance of sleep in regulating liver metabolism and homeostasis of the metabolic environment.…”
Section: Discussionmentioning
confidence: 62%